SCREENING AND FACTOR ANALYSIS OF DELAYED TREATMENT OF UNDESCENDED TESTIS (UDT) IN EARLY CHILDHOOD - Subrata, Gabriella; Daryanto, Besut; Nurhadi, Pradana (Indonesian Urological Association, 2025)
Objective: To determine the prevalence of undescended testis (UDT) cases in the integrated health service post of the Wagir health center working area, the level of parental knowledge of UDT disorders, and to find out what factors affect the delay in UDT treatment. Materials and Methods: Physical examination by a urology specialist education doctor and distributing questionnaires to parents of toddlers with UDT disorders which were then analyzed with SPSS software using the chi square method followed by the binary logistic regression method. Result : Factors that were found to significantly affect the delay in UDT treatment included antenatal care history (sig. = 0.023) and parental knowledge about UDT (sig.=0.044). Factors found to be less significant in influencing the delay in UDT treatment included affordability of health facilities, insurance ownership, parents' monthly income, latest education, and family history. Conclusion: The prevalence of this with the majority of the population having poor knowledge about UDT. The factors that most influence the delay in treatment are antenatal care history and parental knowledge about UDT Keywords: Undescended Testis (UDT), Delayed Treatment, Parental Knowledge, Delayed Factors Objective: This study aims to determine the prevalence of undescended testis (UDT) cases in the integrated health service post of the Wagir health center working area, the level of parental knowledge of UDT disorders, and to find out what factors affect the delay in UDT treatment. Material & Methods: Physical examination by a urology specialist education doctor and distributing questionnaires to parents of toddlers with UDT disorders which were then analyzed with SPSS software using the chi square method followed by the binary logistic regression method. Results: Factors that were found to significantly affect the delay in UDT treatment included antenatal care history (sig. = 0.023) and parental knowledge about UDT (sig.=0.044). Factors found to be less significant in influencing the delay in UDT treatment included affordability of health facilities, insurance ownership, parents' monthly income, latest education, and family history. Conclusion: The prevalence of this with the majority of the population having poor knowledge about UDT. The factors that most influence the delay in treatment are antenatal care history and parental knowledge about UDT. Keywords: Undescended Testis (UDT), parental knowledge, physical examination